PATRIARCHAL CULTURE IN THE NOVEL AL JINNYAH BY GHAZI AL QASAIBI - Syaiful Milal, Mukhamad (Prosiding Konferensi Nasional Bahasa Arab, 2023)
This research will discuss patriarchal culture and women's struggle to maintain their existence in the novel Al Jinniyah by Ghazi al Qasaibi. This research uses a qualitative method with a feminist literary criticism approach based on the theory of existentialist feminism according to Simone de Beauvoir. The data source in this research is a novel entitled Al Jinniyah. This research shows that the forms of patriarchal culture contained in the novel Al Jinniyah are as follows; first, domestication of women in the household; second, patriarchal hegemony. In addition, this study also sees through the representation of the main character's wives that the struggle of women in maintaining their existence is by means of; first, rejection of the domination of power; second, representation of beauty myths; third, portrait of narcissism; fourth, equality in the domestic sphere. All of these forms of struggle symbolically reflect the existence of women in the patriarchal culture of Arab society. In Simone's view, women's existence depends on the awareness of others as others are controlled by the subject, not as a whole human being for their own existence